2015
DOI: 10.1021/mp500539g
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Albendazole Desmotropes by Solid-State NMR Spectroscopy

Abstract: Characterization of the molecular structure and physicochemical solid-state properties of the solid forms of pharmaceutical compounds is a key requirement for successful commercialization as potential active ingredients in drug products. These properties can ultimately have a critical effect on the solubility and bioavailability of the final drug product. Here, the desmotropy of Albendazole forms I and II was investigated at the atomic level. Ultrafast magic angle spinning (MAS) solid-state nuclear magnetic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
53
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

5
4

Authors

Journals

citations
Cited by 48 publications
(62 citation statements)
references
References 53 publications
8
53
1
Order By: Relevance
“…Particularly, one-dimensional proton-enhanced 13 C (or 15 N) CPMAS NMR spectroscopy has become an indispensable and essential tool for the study of physical and chemical properties of various non-soluble and non-crystalline solids such as bone [5,6], membrane proteins [79], amyloid fibrils [10,11], polymers [1214], pharmaceutical compounds [15,16], etc. Despite that CP leads to a substantial gain in signal sensitivity with an enhancement factor of γ H /γ X , the polarization transfer efficiency can be severely limited by weak heteronuclear dipolar couplings, as in the case of dynamic systems or semi-solids where molecular motions suppress dipolar couplings [17].…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, one-dimensional proton-enhanced 13 C (or 15 N) CPMAS NMR spectroscopy has become an indispensable and essential tool for the study of physical and chemical properties of various non-soluble and non-crystalline solids such as bone [5,6], membrane proteins [79], amyloid fibrils [10,11], polymers [1214], pharmaceutical compounds [15,16], etc. Despite that CP leads to a substantial gain in signal sensitivity with an enhancement factor of γ H /γ X , the polarization transfer efficiency can be severely limited by weak heteronuclear dipolar couplings, as in the case of dynamic systems or semi-solids where molecular motions suppress dipolar couplings [17].…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21] As a result, an increasing number of studies utilizing protondetection NMR under ultrafast MAS have been reported in the recent years. [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] Novel pulse sequences under ultrafast MAS conditions have been demonstrated for the measurement of heteronuclear dipolar coupling and chemical shift aniosotropy. 26,[38][39][40][41] The unique combination of 1 H-1 H dipolar recoupling and ultrafast MAS has made proton-detected solidstate NMR methods to be quite attractive and enabled the possibility of using 1 H-1 H dipolar coupling for potential structural studies.…”
Section: Introductionmentioning
confidence: 99%
“…Solid‐state NMR spectroscopy has been playing very important roles by rendering substantial insights into the atomic‐resolution molecular structures and dynamics of various types of solids including polymers, protein assemblies, bone, amyloid aggregates, and pharmaceutical compounds, However, its poor sensitivity has severely limited the application of this mighty technique. In fact, many exciting applications cannot utilize the benefits of sophisticated multidimensional solid‐state NMR techniques.…”
Section: Figurementioning
confidence: 99%